Behind Closed Doors: Discourses and Strategies in the European Securitized Borderlands in Moldova, Serbia and Ukraine. Issue 5 (20th October 2019) - Danero Iglesias, Julien
ABSTRACT: Since the enlargements of 2004 and 2007 European integration has brought about major changes for the citizens of Central and Eastern Europe, such as a process of re-bordering. The accession of countries in the region to the EU, and for some to the Schengen Area, has strengthened borders where there was previously fluidity. This is the starting point of a research on the populations located on the non-EU side of the EU border. The paper takes as a case study Romanian populations living in border regions in Moldova, Serbia, and Ukraine to investigate local discourses of the border and strategies put forward to overcome what is often perceived as an artificial obstacle. Collected through an ethnography of "ordinary citizens, " the data demonstrate how the securitization of the EU border has led to the development of instrumental identities and practices of those living on the "wrong" side of the EU borders.